Supporting the modern research workflow. Issue 1 (27th December 2016) - Grguric, Ekatarina; Davis, Hilary; Davidson, Bret
ABSTRACT: Libraries are uniquely positioned to support the quickly shifting landscape of modern research practice. The NCSU Libraries has paired user research approaches with iterative design practice to determine contextually relevant services to support researchers. This poster will showcase two case studies as examples of successful avenues of support through library services, the user research and application of frameworks that supported the development of these services, and the project management methodology that applied research to practice. Each case study will outline strategies used to develop services that support modern research practice through the investigation of a complex problem space.